PENGUKURAN TINGKAT KEUNTUNGAN DAN FAKTOR YANG MEMPENGARUHINYA PADA UMKM DONATAWA - Faraiddin, Nurfadillah Najwa; Fathurrahman, Maulana (Lembaga Pengembangan Kinerja Dosen, 2023)
Business is a productive activity carried out by companies or people in the economic sector with the aim of gaining profit or profit. One of the businesses that we often hear about is UMKM, UMKM is a micro, small or medium business carried out by companies or individuals who stand alone. One of the MSMEs that we encountered was the Donatawa UMKM. This MSME focuses on the field of bakery sales. We chose this Donatawa store as our research material with the aim of analyzing the level of profit they earned during early 2023, and what factors influenced it. The method that we used in this research is a qualitative method that we did by interviewing Ms. Nisa as the owner of the Donatawa shop, which we carried out on May 19, 2023. And the result is that the profit every month at the beginning of 2023 is January, February, March, and In April, the Donatawa shop experienced a decrease and increase every month, this was due to an event that month. And the average profit they get during the beginning of 2023 is 24.3 million